2020
DOI: 10.1002/app.49184
|View full text |Cite
|
Sign up to set email alerts
|

Flexible poly(styrene‐ethylene‐butadiene‐styrene) hybrid nanofibers for bioengineering and water filtration applications

Abstract: Among the thermoplastic elastomers that play important roles in the polymer industry due to their superior properties, styrene‐based species and polyurethane block copolymers are of great interest. Poly(styrene‐ethylene‐butadiene‐styrene) (SEBS) as a triblock copolymer seems to have the potential to meet many demands in different applications due to various industrial requirements where durability, biocompatibility, breaking elongation, and interfacial adhesion are important. In this study, the SEBS triblock c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 49 publications
(68 reference statements)
0
11
0
Order By: Relevance
“…The market for SEBS materials keeps expanding. 24,26 It is also reported that SEBS can be meltspun into fibers. 10,12,27 reported.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The market for SEBS materials keeps expanding. 24,26 It is also reported that SEBS can be meltspun into fibers. 10,12,27 reported.…”
Section: Introductionmentioning
confidence: 98%
“…Also, SEBSs are steam sterilizable so that they become good alternatives for PVC to produce medical products, such as tubing for peristaltic pumps. The market for SEBS materials keeps expanding 24,26 . It is also reported that SEBS can be melt‐spun into fibers 10,12,27 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Over the past few years, membrane separation technology has received great attention as one of the most promising methods for water and wastewater treatment and producing high quality water. [6][7][8][9][10] Polymeric membranes with robust chemical, mechanical and thermal stabilities and ability to effectively remove contaminants are commonly used in water and wastewater treatments. 11,12 The trade-off relationship between selectivity and permeability as well as membrane fouling is critical issues in the application of polymeric membranes in water and wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Strategies like water reuse have been used to meet rising fresh water demand 1–5 . Over the past few years, membrane separation technology has received great attention as one of the most promising methods for water and wastewater treatment and producing high quality water 6–10 …”
Section: Introductionmentioning
confidence: 99%
“…Due to their characteristics of high specific surface area and aspect ratio, nanofibers are widely used in tissue engineering [1,2], filtration [3], wound dressings [4], soundabsorbing materials [5], food preservation [6] and so on. At present, the technologies for preparing nanofibers have self-assembly [7], phase separation [2], electrospinning (ES) [8][9][10][11], and so on.…”
Section: Introductionmentioning
confidence: 99%